Penerapan Stochastic Frontier Analysis untuk Estimasi Efisiensi Industri Manufaktur di Indonesia Tahun 2022 - Parulian, Firman Emmanuel Declarantius; Harum, Nisrina Sekar; Aditya, Randy Daffa; Yuliana, Rita (Seminar Nasional Official Statistics, 2025)
The manufacturing industry plays a crucial role in Indonesia’s economic system due to its significant contribution to GDP. However, the sector’s share of GDP has been declining over the years. Therefore, efficiency and productivity levels remain key challenges that must be addressed. This study aims to estimate the technical efficiency of the manufacturing industry and analyze the factors affecting its inefficiency across 34 provinces in Indonesia using Stochastic Frontier Analysis (SFA) in 2022. Unlike previous studies that focus on inter-industry or industrial classification analysis, this research adopts a regional perspective. The results indicate that capital and labor have a positive and significant effect. Furthermore, average years of schooling and fuel consumption in the manufacturing industry significantly affect technical inefficiency. Province with the highest technical efficiency is West Java, while the lowest is in East Nusa Tenggara.